Age hardening in (Ti1 − xAlx)B2 + Δ thin films. (15th January 2017) - Mockute, A.; Palisaitis, J.; Alling, B.; Berastegui, P.; Broitman, E.; Näslund, L.-Å.; Nedfors, N.; Lu, J.; Jensen, J.; Hultman, L.; Patscheider, J.; Jansson, U.; et al.
Abstract: Thin films of (Ti0.71 Al0.29 )B2 + 1.08 have been deposited by magnetron sputtering. Post-deposition annealing at 1000 °C for 1 h results in increased hardness and elastic modulus, from 32 to 37 GPa and from 436 to 461 GPa, respectively. In both as-deposited and annealed states the films adhere well to the substrate, indicating no considerable internal stress. The initial high hardness is attributed to a columnar microstructure consisting of crystalline (Ti, Al)B2 columns separated by an amorphous B matrix. The observed age hardening corresponds to phase separation within the (Ti, Al)B2 columns including the formation of Ti-deficient crystallites within the grain interior upon annealing. Graphical abstract: